Quantum modeling of threshold voltage in Ge dual material gate (DMG) FinFET. (September 2019) - Saha, Rajesh; Bhowmick, Brinda; Baishya, Srimanta
Abstract: An analytical model for threshold voltage of Ge dual material gate (DMG) FinFET by self consistently solving 3D Poisson's and 2D Schrödinger's equation is developed. The model includes the quantum effects as well. The potential distribution in the channel region is developed by solving 3D Poisson's equation. The expression for wave function and quantized energy levels are derived by solving 2D Schrödinger's equation. The model for inversion charge is derived by using the expression of quantized energy levels. The threshold voltage model is derived by equating inversion charge with the threshold charge estimated from TCAD simulator. The proposed models are validated with a numerical simulator for a wide range of geometrical parameter and drain bias values.